GRACE gravity analysis exploring climatic influences on mass changes in the Antarctic Peninsula - A. Romero; A. Romero; A. Richter; A. Richter; A. Juarez; A. Juarez; F. Suad Corbetta; F. Suad Corbetta; E. Marderwald; E. Marderwald; P. Granovsky; T. Döhne; et al. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Antarctic ice-mass balance is key to project sea-level changes, to assess future shifts in the global water cycle and ocean circulation, and to predict the fate of the White Continent. The ice mass of the Antarctic Peninsula is sensitive to the atmospheric and ocean circulation. The geographical conditions pose a challenge for modelling surface mass balance in this area. We use GRACE and GRACE Follow-On satellite gravimetry to derive a mass variation time series for the Antarctic peninsula region 2002–2024. We investigate whether these mass variations correlate with a surface mass balance model or with global climate indexes. Our analysis indicates a mass loss over two decades, mainly due to a period of enhanced mass-loss rate between 2007 and 2015. Our results suggest that interannual mass variations are primarily controlled by the surface mass balance which is influenced by the El Niño-Southern Oscillation phenomenon.